“A ROMANCE IN LETTERS” OF SHMELEV AND BREDIUS-SUBBOTINA: PARADOXES OF SMELLS AND AROMAS OF LOVE - Valentina D. Narivskaya (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article considers the correspondence of the famous writer Ivan Shmelev (1873–1950) with Olga Bredius-Subbotina (1904–1959). Their acquaintance took place in the emigration in a “reader-admirer” format. It was a difficult period in Shmelev’s life due to the execution of his single son, the force to emigrate, the death of his wife. The writer’s state evoked sensation of parting with the world. Unexpected correspondence with Bredius-Subbotina, her admiration for the creative work of a talented master of literature revived the desire to live and create. This time it was correspondence, which over time gained special significance for Shmelev, gave him the opportunity to be heard in his stories about the tragic feelings with which he had lived for years. Among the most painful one was the theme of Crimea, which broke out in correspondence with the deeply stored state – the memory of the Crimean smells, as it turned out, was more stable, strong and therefore dear to the writer’s heart. This implied a corresponding reaction of the addressee. But Bredius-Subbotina remained somewhat indifferent to the topic of Crimea, nevertheless she was able to offer a new format of correspondence on the wave of Crimean smells favourite by Shmelev. In the letters by Bredius-Subbotina the accents were shifted to the experience of pleasure of flower aromas and smells. Shmelev accepted this proposal without giving up on the Crimean oxymoronic meanings, multiplying them by the smell of grapes and roses, as a challenge to the abnormal world. Bredius-Subbotina was no less persistent in her desires, so with special force turned “scents of life” into correspondence, i.e. scents of favourite flowers, thereby arousing Shmelev’s impression through his sense of smell, helping him to return to his youth, to boyishness, to a seemingly forgotten state. Thus, in 1941, in the midst of the tragic events of the World War II the traditional theme of world literature love and war revived in correspondence between Shmelev and Bredius-Subbotina. The moment came when Shmelev realized that Olga Aleksandrovna was his last love, and his correspondence with her was a “romance in letters”; he, as a writer, created his last work of art, which would be read by descendants. Therefore, Shmelev not only restored the traditions of world and Russian love epistolarians, but also brought his experience back to his youth. He was fascinated by the possibility of exchanging flowers and floral aromas, which contributed to the intensive work of the imagination. In his letters, the writer created floral sketches of his beloved one, and then wrote an etude “Girl with Flowers”, which he managed to convey. Hyacinths, bells, lilies, peas, lilacs were transferred from Paris to Holland and became symbols of passionate love. Shmelev and Bredius-Subbotina turned to another cultural tradition, and therefore received letters with the smell of French perfume, which created a sense of bodily intimacy, a special state of love. Flowers, floral fragrances, French spirits mixed in love correspondence determined its style and presented a unique image of love for the twentieth century.